Pilot Executive Functioning Intervention in Epilepsy: Behavioral and Quality of Life Outcomes. (12th January 2021) - Modi, Avani C; Mara, Constance A; Schmidt, Matthew; Smith, Aimee W; Turnier, Luke; Wade, Shari L
Abstract: Objective: To examine changes in emotional and behavioral functioning and health-related quality of life (HRQOL) following a web-based executive functioning (EF) intervention open pilot trial (e.g., Epilepsy Journey) for adolescents with epilepsy. Methods: Adolescents with an established diagnosis of epilepsy, EF deficits, and without developmental disorders participated in a single-arm trial of Epilepsy Journey. Epilepsy Journey is a gamified, online learning environment comprised of 10 learning modules targeting EF deficits (e.g., working memory, organization) and tailored to epilepsy with accompanying telehealth problem-solving sessions. Adolescents completed questionnaires assessing emotional and behavioral functioning and HRQOL at baseline, posttreatment, and 2 follow-ups . Longitudinal mixed models and logistic regression analyses were used for these secondary analyses. Results: 39 adolescents were recruited for Epilepsy Journey ( M age =15.3 years; 67% female; 87% White: Non-Hispanic; 39% experienced seizures in the past 3 months). Preliminary data indicate significant improvements in caregiver-reported Externalizing symptoms, Behavioral Symptom Index scores and Adaptive Skills from baseline to 5-month follow-up. Significant improvements were observed for caregiver-reported Mood/Behavior and self-reported Impact, Cognitive Functioning, Executive Functioning, and Sleep subscales of the PedsQL Epilepsy Module. Clinically significant improvements (e.g., clinical/at-risk to normative levels) in behavioral and quality of life domains were also noted. Conclusion: Epilepsy Journey appears to contribute to changes in emotional and behavioral functioning and HRQOL in adolescents with epilepsy. Given the proof of concept trial format of this study, an important future direction is to conduct a randomized controlled trial with a larger, generalizable cohort of adolescents with epilepsy.